B- Lynch suture as prophylaxis measure or therapeutics measure in management of postpartum haemorrhage - fahad al-assady, Nadia saddam (International Journal of Psychosocial Rehabilitation, 2020)
-The main objective of this study is to explain to what extent B-Lynch suture is a therapeutic technique that helps in controlling and maintaining uterine bleeding and thus maintaining fertility. In this paper, I will discuss the effectiveness of B-Lynch suture and its success in controlling the pulse of the pelvis and applying it to several cases without any problems or complications. A study was conducted on observation and monitoring of 20 patients who underwent B-Lynch stitching in the obstetrics section. It was noted to what extent patients needed to transfer blood or hysterectomy due to the loss of a large amount of blood during the birth. Later, patients were followed up to see how far the complications might have been, and whether there were health problems related to the mother’s condition or infertility problems. B- Lynch suturing was 100% successful as a preventive measure or therapeutic measure in managing postpartum haemorrhage. No patients were found to need a hysterectomy and all women had a mild puerperium not troubled. There is no evidence of serious complications for patients during the follow-up period. B-Lynch is an important and effective technique that can save the lives of many patients and protect them from large-scale blood loss or hysterectomy. This is an important procedure in surgery science and fertility in women. B-Lynch should be used when medical management fails before seeking hysterectomy.